EHR Systems and Blockchain: Potentials, Challenges and the Road Ahead: ConV2X 2023 CME Session - Poteet, Jim; Gault, Mike; Khurshid, MD, PhD, Anjum; Sivagnanam, Suresh; Norta, PhD, Alex; Treiblmaier, PhD, Moderator: Horst (Blockchain in Healthcare Today, 2024)
Panelists discuss blockchain technology use for electronic health records, and specifically delve into the benefits that blockchain brings to EHRs, but also discuss what its pitfalls and limitations are; including presenting perspectives from academia, and examples from practitioners. Learning Objectives Understand the potential applications of blockchain for electronic health records (EHRs). Explore the benefits and challenges of implementing blockchain for EHRs, including security, interoperability, privacy, and data integrity. Identify key use cases and real-world examples of blockchain implementation in healthcare and EHR management. Analyze the potential impact of blockchain on improving healthcare data exchange, patient consent management, and medical research. Discuss the regulatory and legal considerations associated with using blockchain in healthcare, such as compliance with data protection laws and standards. Examine the role of smart contracts and decentralized applications (DApps) in enhancing EHR management and patient control over their health information. Assess the scalability and performance limitations of blockchain technology in handling large-scale healthcare data and high transaction volumes. Evaluate potential cost savings and efficiency gains achieved through blockchain implementation in EHRs, considering factors such as data access, auditability, and administrative overhead. Discuss the future prospects and challenges of integrating blockchain with existing healthcare systems, standards, and infrastructure to achieve widespread adoption and interoperability.